Multilevel Stabilization Screws Prevent Proximal Junctional Failure and Kyphosis in Adult Spinal Deformity Surgery: A Comparative Cohort Study. Issue 3 (14th March 2022) - Kaufmann, Ascher; Claus, Chad; Tong, Doris; Hanson, Connor; Carr, Daniel; Houseman, Clifford; Soo, Teck-Mun
Abstract : BACKGROUND: Proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) occurred in up to 40% of patients with adult spinal deformity (ASD) who underwent open thoracolumbar fusion. Proximal stabilization techniques have been investigated to prevent PJK/PJF without conclusive results. OBJECTIVE: To demonstrate reductions in PJK/PJF with multilevel stabilization screws (MLSSs). METHODS: This observational longitudinal cohort study compares MLSSs with standard instrumentation. We reviewed the charts of consecutive patients with ASD undergoing open thoracolumbar fusion (>3 levels, extending cranially above T6 and caudally below L1) from 2009 to 2017 and were followed for >2 yr postoperatively. We defined PJF using the International Spine Study Group criteria and PJK as a Cobb angle increase >10°. We defined the upper instrumented vertebra as the most cephalad vertebral body with bilateral MLSSs. Confounders, MLSS-specific complications, and radiographic outcomes were collected. We evaluated comparability between groups using univariate analyses. We adjusted for covariates by using multivariable regressions modeling PJF and PJK separately with a P -value < .00625 considered significant after the Bonferroni correction. Sensitivity analysis accounted for those lost to follow-up. RESULTS: Seventy-six patients (50 MLSS vs 26 controls) were included. MLSS patients were significantly older (64.5 ± 8.9 vs 54.8 ± 19.9 yr, P = .024) and had significantly lower PJF incidence (10.0% vs 30.8%, P = .023) and less kyphosis (1.3° ± 5.3° vs 5.2° ± 6.3°, P = .014). Multivariable analysis demonstrated a significant independent association between MLSSs and decreased odds of PJF (odds ratio: 0.11, 0.02–0.53, P = .006). Perioperative complications did not significantly differ between cohorts. CONCLUSION: MLSSs are safe and efficacious in reducing PJF/PJK in patients with ASD undergoing open thoracolumbar fusion.